(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SUMARIO: 1. La implementación del m.p. Mitis Iudex - 2. La salus animarum y la reforma de los procesos de nulidad matrimonial - 2.1. La salus animarum, principio inspirador - 2.2. ¿Cómo contribuye a la salus animarum el proceso judicial? - 3. La centralidad del Obispo diocesano. Challenges presented by the conversion of justice in the Church in the light of m.p. Mitis Iudex Dominus Iesus ABSTRACT: In these pages I will try to show that the motive leading to the reform of the m.p. Mitis Iudex and the recovered centrality of the Bishop judge are questions that should not be limited exclusively to the processes of marriage nullity, since they are so important that they go beyond these procedural limits; on the contrary, they should project their influence not only on the norms that regulate the ordinary processes but also on the very organization of justice in the Church. The conversion of justice that the Roman Pontiff has initiated with the m.p. Mitis Iudex, therefore, involves the rest of the causes and canonical procedural law itself.